Features of the Belarusian economic model: x - Egorov, Alexandre (Management and Administration Journal, 2021)
At the beginning of the XXI century Belarus is still proceeding to suffer from the consequences of a social experiment, that had been put a hundred years ago in the Russian Empire, that later transformed into the Soviet Union. Due to some objective and subjective reasons, Belarus uses a rare economic model, which is not similar to the economic models of the neighboring countries. The official representatives of the Economics call it «the Belarusian economic model that has proved it effectiveness». Meanwhile, there is no one self-consistent explanation of the model. Neither in the official documents and special researches, nor in any university textbooks exact features and principles of the model functioning, can be found. The term is used by default. The model is functioning like “terra incognita” - according to the not finally understood laws.